2000
DOI: 10.1086/317597
|View full text |Cite
|
Sign up to set email alerts
|

Human Immunodeficiency Virus Transactivator Protein (Tat) Stimulates Chemotaxis, Calcium Mobilization, and Activation of Human Polymorphonuclear Leukocytes: Implications for Tat‐Mediated Pathogenesis

Abstract: The extracellular activities of the human immunodeficiency virus (HIV) transactivator protein (Tat) include induction of angiogenesis and stimulation of monocyte migration. Here it is shown that polymorphonuclear leukocytes (PMNL), mostly neutrophils, rapidly invade in response to Tat in vivo and initiate the formation of new vessels. In vitro, Tat was chemotactic for PMNL and induced calcium (Ca(2+)) mobilization. Tat proteins with inactivating substitutions in the arginine-glycine-aspartic acid or basic doma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0
2

Year Published

2003
2003
2011
2011

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(43 citation statements)
references
References 54 publications
0
41
0
2
Order By: Relevance
“…These initial mechanistic insights encouraged us to investigate whether the effects registered in vitro translate efficaciously in vivo in the restraint of inflammatory cell recruitment. The first approach used a recently optimized model in which the inflammatory infiltrate is responsible for induction of the angiogenic process, in that neutrophil depletion abrogated the angiogenic response induced by CXCR2 ligands (Benelli et al, 2000). Using IL-8 as chemoattractant, we were able to induce a rapid and intense infiltration of neutrophils into Matrigel plugs in mice, accompanied by angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These initial mechanistic insights encouraged us to investigate whether the effects registered in vitro translate efficaciously in vivo in the restraint of inflammatory cell recruitment. The first approach used a recently optimized model in which the inflammatory infiltrate is responsible for induction of the angiogenic process, in that neutrophil depletion abrogated the angiogenic response induced by CXCR2 ligands (Benelli et al, 2000). Using IL-8 as chemoattractant, we were able to induce a rapid and intense infiltration of neutrophils into Matrigel plugs in mice, accompanied by angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Human PMN response to 10 Ϫ7 M fMLF or 50 ng/ml IL-8 was measured by seeding 2 ϫ 10 6 cells, in serum-free medium with or without Hyp-DCHA, onto the top compartment of 8-mm-diameter Boyden chambers; 5-m pore-size filters, uncoated or coated with gelatin (chemotaxis) or Matrigel (chemoinvasion), were separating the bottom compartment filled with medium containing one (or none) of the above-mentioned chemoattractants; after 40 or 120 min at 37°C, respectively, migrated cells were collected and counted under a microscope (Benelli et al, 2000). PMNs were also seeded (5 ϫ 10 5 ) onto 96-well plates, incubated in 5% CO 2 , air at 37°C in 90 l of DMEM without phenol red and fetal calf serum, and with or without Hyp-DCHA.…”
Section: Methodsmentioning
confidence: 99%
“…Among HIV-1 proteins, Tat exhibits strong monocyte chemotactic properties (2,3); the increased migration of the activated monocytes to the brain is strongly correlated with HAD (23). Therefore, we evaluated structural and functional aspects of Tat that could influence monocyte chemotactic function and explain the low frequency of HAD.…”
Section: Human Immunodeficiency Virus Type 1 (Hiv-1)-associated Demenmentioning
confidence: 99%
“…Initial studies in the in vivo Matrigel model suggested that these cells might play a lead role in vessel formation induced by lamininderived SIKVAV peptide, which promotes angiogenesis weakly in neutropenic mice related to control mice (4). Furthermore, the HIV viral transactivator protein Tat activates neutrophils as part of its angiogenic activity (5). In skin carcinogenesis models, the requirement for MMP2 expression in tumor development was localized in a bone marrow compartment later identified as granulocytes (6).…”
Section: Evidence For the Role Of Innate Immune Cells In Physiologic mentioning
confidence: 99%